MicroRNAs in neural crest development and neurocristopathies. (29th April 2022) - Antonaci, Marco; Wheeler, Grant N.
Abstract : The neural crest (NC) is a vertebrate-specific migratory population of multipotent stem cells that originate during late gastrulation in the region between the neural and non-neural ectoderm. This population of cells give rise to a range of derivatives, such as melanocytes, neurons, chondrocytes, chromaffin cells, and osteoblasts. Because of this, failure of NC development can cause a variety of pathologies, often syndromic, that are globally called neurocristopathies. Many genes are known to be involved in NC development, but not all of them have been identified. In recent years, attention has moved from protein-coding genes to non-coding genes, such as microRNAs (miRNA). There is increasing evidence that these non-coding RNAs are playing roles during embryogenesis by regulating the expression of protein-coding genes. In this review, we give an introduction to miRNAs in general and then focus on some miRNAs that may be involved in NC development and neurocristopathies. This new direction of research will give geneticists, clinicians, and molecular biologists more tools to help patients affected by neurocristopathies, as well as broadening our understanding of NC biology.